Recyclable amberlyst-70 as a catalyst for biginelli reaction: an efficient one-pot green protocol for the synthesis of 3,4-dihydropyrimidin-2(1H)-ones - Chandak, Hemant S.; Lad, Nitin P.; Upare, Pravin P. (Catalysis Letters, 2009)
An environmentally benign aqueous protocol for the synthesis of 3,4-dihydropyrimidin-2(1H)-ones using Amberlyst-70 as a recyclable catalyst has been developed. The use of resinous, nontoxic, thermally stable and inexpensive Amberlyst-70, as a recyclable heterogeneous catalyst, makes the process simple with negligible chemical waste. Thus renders this method an environmentally acceptable synthetic tool for Biginelli reaction.
Keywords: Amberlyst-70; Biginelli reaction; green chemistry; heterogeneous catalysis